Microdot Accumulation in the Anterior Cornea with Aging - Quantitative Analysis with in Vivo Confocal Microscopy - Utheim, Tor Paaske; Chen, Xiangjun; Fricke, Otto; Bergersen, Linda Hildegard; Lagali, Neil (Current eye research, 2020)
Degenerative 'microdot' deposits in healthy and hypoxic corneas are believed to represent lipofuscin-like material aggregation in the stroma. To accurately assess microdot deposits in a clinical setting, we sought to quantify these deposits for the first time using the non-invasive clinical imaging technique of in vivo confocal microscopy (IVCM). The corneas of 102 healthy subjects aged 15-88 years were examined by IVCM and microdot density was quantified using a 6-point grading scale by two masked, trained examiners. Microdot density was analyzed with respect to age, sex and stromal depth, and inter-eye and inter-observer differences were evaluated. In healthy subjects, microdot density decreased from the anterior to posterior stroma, with the greatest accumulation observed in the most anterior stroma (subepithelial region). In this region, microdot density correlated strongly with age (P < .0001), with increased microdot deposition in older subjects (>60 years) relative to younger ones (<45 years) (P < .001). Microdot density between eyes of the same subject was highly correlated (r = 0.92, P < .0001), while no association with sex was noted (P ≥ 0.05). The mean inter-observer difference in microdot assessment was 0.62 ± 0.09 grades, with a high correlation of grading between observers (r = 0.77, P < .0001). IVCM can be used to non-invasively quantify microdot deposits in the subepithelial corneal stroma with good inter-observer reproducibility. Microdot assessment may provide a novel means of quantifying age-related or pathologic degeneration of the corneal stroma in a clinical setting.